Institutional Arbitration and Ad Hoc Arbitration: Two Sides of the Same Coin (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Arbitration, in general, is a means of resolving disputes between individuals outside the court. Arbitration is sought for the numerous advantages it offers, including the ability for the parties to determine the method of dispute resolution from start to finish, such as specifying the applicable law and choosing the arbitrators. Arbitration is divided into two main categories based on the procedures followed: private arbitration and institutional arbitration.In this research, we discussed private arbitration and institutional arbitration during the phase prior to the issuance of the award, highlighting the differences between the two, as well as the phase following the issuance of the award and focusing on the enforcement of the award.The central issue revolves around whether individuals resorting to arbitration as a means of resolving their disputes prefer one type of arbitration over the other—private or institutional.We reached several conclusions:• Private arbitration and institutional arbitration represent distinct types of arbitration; this distinction arises from differences in the procedures followed in each type. The method of rendering an award does not differ, whether it is private or institutional.• In both types, the principle of autonomy of will generally prevails in determining the procedures followed.• In both types, it is not permissible to agree to any procedure that contravenes international public policy or the public policy of the country of enforcement.• The authority responsible for selecting arbitrators must consider the legal and contractual conditions when making appointments. In cases of disagreement, the right to appoint falls to the judiciary for private arbitration, while an institutional arbitration center will handle this for institutional arbitration.• If there is no agreement on the law governing the procedures, in private arbitration, the law of the seat of arbitration is often applicable for enforcement purposes; in contrast, the rules of the arbitration institution will apply in institutional arbitration.